Unraveling Herpes Zoster Vaccine Hesitancy, Acceptance, and Its Predictors: Insights From a Scoping Review - Xiaolong Wang; Shuhui Shang; Enming Zhang; Zhengyue Dai; Yufei Xing; Jiale Hu; Yaojuan Gao; Qiong Fang (Frontiers Media S.A., 2024)
ObjectivesHerpes zoster vaccination is critical in preventing herpes zoster virus infection and its associated consequences. Despite its relevance, global herpes zoster immunisation coverage remains alarmingly low. Understanding the factors that drive vaccine scepticism and acceptance is crucial for increasing immunisation rates and improving public health outcomes.MethodsThis scoping review, following Joanna Briggs Institute guidelines, included 18 studies examining vaccine hesitancy, acceptance, and associated factors. Meticulous data analysis revealed hesitancy's intricate dynamics across countries and demographics.ResultsStudies displayed a wide range of acceptance rates (2.8%-89.02%), showcasing the complex interplay of attitudes and behaviors towards vaccination. Reasons for vaccine refusal were repeatedly identified in this setting, including worries about potential adverse effects, views of vaccine necessity, and vaccine supply constraints. Notably, individuals' patterns of vaccine acceptance and hesitancy differed among countries, vaccines, and vaccination-related factors.ConclusionAddressing acceptance hurdles by improving accessibility, providing accurate information, and strengthening healthcare recommendations is crucial. Understanding the multifaceted factors influencing hesitancy allows for targeted interventions, elevating immunization rates and enhancing public health globally.